2008
DOI: 10.1002/ep.10279
|View full text |Cite
|
Sign up to set email alerts
|

Process studies for development of adsorption technology for furfural recovery from waste water

Abstract: Lube refineries in India are facing pollution problems associated with the occasional loss of furfural from their solvent recovery column bottoms in the extraction plant, which constitute both an economic loss and an environmental hazard. Although earlier studies on furfural removal by adsorption on polymeric resins concentrated on equilibrium and kinetic/breakthrough measurements in small diameter columns in the adsorption, the regeneration of the loaded resin adsorbent has not been given adequate attention. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Fargues et al made a thorough comparison based on single component isotherms and breakthrough curves of ion exchange (weak and strong) resins with polymeric adsorbers, all with styrene–DVB based matrices. Although the good furan adsorption on the styrene–DVB resin is consistent with the findings of others, the low adsorption of furans on styrene based anion exchange resins is not consistent with the findings of others . Other research on this subject only examines the effect of adding different resins to the hydrolysate on the effectiveness of the fermentation .…”
Section: Introductionmentioning
confidence: 42%
See 1 more Smart Citation
“…Fargues et al made a thorough comparison based on single component isotherms and breakthrough curves of ion exchange (weak and strong) resins with polymeric adsorbers, all with styrene–DVB based matrices. Although the good furan adsorption on the styrene–DVB resin is consistent with the findings of others, the low adsorption of furans on styrene based anion exchange resins is not consistent with the findings of others . Other research on this subject only examines the effect of adding different resins to the hydrolysate on the effectiveness of the fermentation .…”
Section: Introductionmentioning
confidence: 42%
“…Several authors showed that these toxins can be removed by adsorption. Polymeric adsorbers, cat‐ and anion exchange resins (weak and strong), zeolites and activated carbon have shown to remove these toxins. Because of regeneration, stability and capacity, polymeric adsorbers (resins), with and without ion exchange groups, are considered most promising for adsorption of these toxins …”
Section: Introductionmentioning
confidence: 99%
“…Other authors studied the desorption using different solvents (e.g. methanol, ethanol, n‐propanol and n‐butanol, acetone) . Although these solvents removed HMF effectively, their strong interaction with the resin, thus introducing another component in the system, is a major drawback.…”
Section: Resultsmentioning
confidence: 99%
“…methanol, ethanol, n-propanol and n-butanol, acetone). 4,28 Although these solvents removed HMF effectively, their strong interaction with the resin, thus introducing another component in the system, is a major drawback. Increased desorption of HMF at higher temperature indicates that desorption with steam could offer a solution for HMF removal.…”
Section: Desorptionmentioning
confidence: 99%
“…In these types of reactions, UV (Ultra Violet) irradiation could be used solely or combined with other oxidizing agents and mineral catalysts. Some of these chemical oxidation processes in the degradation of furfural have been reported as e ective in the removal of various chemical complexes [1][2][3][7][8][9].…”
Section: Introductionmentioning
confidence: 99%